Information Framing and Disposition Effect on Nepalese Investors’ Decision-making Behavior - Subedi, Aashutosh; Dangol, Jeetendra (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study examines the influence of behavioral biases (i.e., specifically, information framing and the disposition effect) on the decision-making behavior of individual investors in the Nepalese stock market. Additionally, the study investigates how years of investment experience moderate these relationships. Design/methodology/approach: A cross-sectional survey design was employed, collecting data from 261 investors actively trading in the secondary market through broker houses in the Kathmandu Valley. Data were gathered using a structured questionnaire and analyzed using SmartPLS 4.0 to causal relationship. Findings: This study demonstrates that the disposition effect significantly shapes investor decision-making, while framing biases show no such impact. Notably, investment experience moderates the disposition effect, amplifying its influence, but does not moderate framing biases, underscoring a nuanced behavioral pattern among investors. Conclusion: The study concludes that while experience helps investors overcome framing-induced irrationalities, the disposition effect remains a persistent bias shaping decision-making in Nepal’s emerging capital market. Implications: This research not only contributes to extending the applicability of behavioral finance theory to frontier markets but also provides essential evidence to inform more targeted investor education initiatives and regulatory policies. Originality/Value: This study adds value by filling an empirical gap through a novel framework that highlights how behavioral biases and investment experience jointly influence investor decision-making in emerging markets. JEL Classification: G11, G41, D81